Pengaruh pola asuh orang tua dan gaya belajarterhadap hasil belajar IPS pada siswa SMP - Sinta Kurniawati; Saiful Amin (Universitas Indraprasta PGRI, 2025)
This research aims to (1) examine the impact of parental parenting on students' social studies learning outcomes, (2) examine the impact of learning styles on students' social studies learning outcomes, and (3) examine the impact of the relationship between parental parenting and learning styles on students'social studies learning outcomes. The methodology was quantitative and employed a correlational strategy, comprising 57 class VIII students at Bani Hasyim Singosari Islamic Middle School. Data was gathered utilizing questionnaires and documentation of UTS scores, then examined utilizing the Two-Way ANOVA method. The outcomes showed that (1) the democratic parenting style (73.68%) significantly influenced learning outcomes (F = 7.221; p = 0.002), (2) the visual learning style (56.14%) also had a significant impact (F = 9.918; p < 0.001), and (3) no significant interaction was found between parenting style and learning style on learning outcomes (F = 0.053; p = 0.818). The study concludes that democratic parenting and visual learning styles independently contribute to improving social studies learning outcomes. Future research should explore additional variables, such as learning motivation or instructional methods, for a more comprehensive understanding of factors affecting student performance.